PERAMALAN HARGA SAHAM PT NFC INDONESIA TBK (NFCX) DENGAN METODE ARIMA - Jovanka Sesilia Meilani; Hesti Selvianingrum; Rizka Febriani Menanti; Gabriella Kasmira Lewar (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2026)
This study aims to analyze and forecast the stock price of PT NFC Indonesia Tbk (NFCX) using the ARIMA method based on RStudio with daily data for 3 years. The analysis includes stationarity testing, differencing, model identification using ACF and PACF, diagnostic testing, and forecasting. The results show that the best model is ARIMA (2,1,0) with an AIC value of -847.7307. The model has good accuracy with RMSE of 0.1405438, MAE of 0.07784609, and MAPE of 2.661817%. Forecasting results indicate that the model can follow historical stock price patterns well and can be used as a tool to support investment decisions. The findings are expected to support investors in making stock investment decisions.